Religious Culture-Based Management in the Focus of Education - Hefniy, Hefniy; Ardiyansyah, Alif Rahman (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
The objective of this research is to enhance the standard of education by employing a religious-cultural approach, specifically a prescriptive approach. This approach entails individuals submitting to, imitating, adhering to, and adopting cultural scenarios dictated by authorities. Additionally, it involves a programmed approach through a learning process where culture develops internally within individuals based on religious beliefs and values. The research employed a qualitative-descriptive methodology. The research findings indicate that the implementation of Religious Cultural Based Management has been effectively executed. Teachers demonstrate strong enthusiasm for implementing religious and cultural norms, while the school principal plays a crucial role in overseeing management methods based on religious culture. The teacher's degree of professionalism is commendable in both the teaching and evaluation domains. The influence of religious culture on management practices impacts work discipline, motivation, and the achievement of optimal work results. Key factors facilitating the integration of Islam culture in schools encompass the proactive involvement of teachers in offering assistance and encouragement, alongside students' recognition of the significance of these endeavors. Nevertheless, there are also constraining elements, such as pupils' lack of awareness, that might result in an uneven distribution of time spent on schooling. In general, the integration of religious culture is executed proficiently and smoothly, with robust facilitating elements and few constraining elements. Implementing religious culture-based management in schools has the capacity to enhance educational standards.